PERILAKU PROSOSIAL DITINJAU DARI ANDROGYNY ROLE DALAM KEGIATAN PRAMUKA PADA ANAK SEKOLAH DASAR - Haniek Farida (LP2M Universitas Sarjanawiyata Tamansiswa, 2017)
The phenomenon of depletion of prosocial behavior has occurred among children, this is influenced by the activities of children's games are dominated by the type of game that is individual. This problem becomes important because the child's age contributes greatly to the formation of personality. This study aims to determine prosocial behavior in terms of androgyny role in scout activities in elementary school children in Yogyakarta. The subjects of the study were V grade children of elementary school. The total subjects involved amounted to 100 children (34 boys and 66 girls). Measuring tool used is prosocial scale and androgini scale. Data were analyzed by using Product Moment Correlation. The results show that there is a significant positive correlation between prosocial behavior with androgyny role in scout activities in elementary school children. This means that the higher the androgyny role the higher the prosocial behavior.